Teaching ideas and classroom activities for health care - Haroun, Lee 4 0 16; Royce, Susan R.; 5 (Australia ;;Clifton Park, NY : Thomson/Delmar Learning, 2004)
Contains a variety of reproducible worksheets and activities designed to help teach basic health care principles, including medical terminology, vital signs, team building, and cultural awareness.
Includes bibliographical references.
Professional;Professional
Keywords: 2 -- 0; 6; Study and teaching;Activity programs.;Study and teaching;Activity programs.;Study and teaching.;Study and teaching. -- Medicine;Medical care;Medicine;Medical care;Creative activities; 20; 2